Investigating crisis resilience pedagogy during the COVID-19 pandemic in Grade 10 business studies classrooms - Mbali Mabaso; Devika Naidoo (Perspectives in Education)
This study investigated the conceptual learning of the Business Studies Curriculum Recovery Plan (BSCRP) during the COVID-19 pandemic. Crisis resilience pedagogy requires teachers to incorporate resilience and flexible strategies to enable learners to cope with unexpected events (Chow, et al., 2020). Informed  by qualitative research methodology, data were collected from document analysis, semi-structured interviews, and classroom observations. Thirteen participants, including teachers, departmental heads, principals, subject advisors, and curriculum designers, were purposively chosen for the study. Crisis resiliencepedagogy attributes adaptability, creativity, connectivity, diversity, and endurance were evident to different degrees. Redesigning the DBE website, trimming the curriculum, and amending instructional materials showed adaptability. Video, podcasts, interactive quizzes, and monitoring Google Forms demonstrated creativity. Connectivity between learners, parents, teachers, principals, and subject advisors was enabled through WhatsApp groups. Microsoft Teams and Zoom were used for meetings. Text, voice, and videobased instruction were employed to meet the diverse needs of the learners. Participants indicated hardships in continuing work duties amidst trauma and bemoaned insufficient and inadequate psychological support during the pandemic. This study extends the crisis resilience pedagogy model by including what learners did and should be doing.